Trabalho, tempo livre e lazer: uma reflexão sobre o uso do tempo da população brasileira - Ferreira, Camila Lopes (2010)
The existence of the human life is connected to work, as much the structure of societty as the formation of a person in the modernity. Work has caused crisis during history, values and cathegories have been changed, demanding a new characterization. This way, work has controlled our social structure, and has reached the point that even our free time and leisure started being integrated into it. This study has as goal to analyze the possibilities of using the time during The Brazilian workers free time. Therefore, the tecnical procedure adopted for this data collection was a documented research. The referring document is based on a nacional research through some sample residences, developed by The Brazilian Geography and Statistic Institute, in 2005. After this study, it can be noticed the necessity of reflection about how the time is used, being it during the free time, the work time or the leisure one, once time contributes the production and the structure of society in a direct way as a whole. Work, free time and leisure are dependable of each other even being found in different contexts. This way is essential to deal with time as a structuring element of the human's life.